The Role of Urban Social Work in Achieving Sustainable Cities: A Discussion on Urban Regeneration in Turkey - Ayalp, Mustafa Çağri; Bolgün, Cemre; Aygüler, Edip (Taylor and Francis, 2025)
[Abstract Not Available]
Keywords: Sustainable development; Social work; Sustainable cities; Urban regeneration; Sustainable city